Zircon SHRIMP U–Pb geochronology of potassic felsic intrusions in western Yunnan, SW China: Constraints on the relationship of magmatism to the Jinsha suture - Lu, Y.; Kerrich, R.; Cawood, P.; McCuaig, T.; Hart, C.; Li, Zheng-Xiang; Hou, Z.; Bagas, L. (Elsevier Science BV, 2012)
The relationship between potassic felsic intrusions, cospatial and cotemporal with potassic mafic magmatism, and strike–slip displacement along the Ailao Shan-Red River shear zone in western Yunnan, SW China has been highly controversial. We report 22 new SHRIMP zircon U–Pb ages from 19 potassic felsic intrusions located as far as 150 km east and 50 km west of the shear zone to constrain temporal relationships. The results show that the felsic intrusions in western Yunnan were emplaced between 36.9±0.3 Ma and 32.5±0.3 Ma. This age range is significantly shorter than previous dating of 38Ma to 23Ma using K–Ar and Ar–Ar methods from 15 intrusions, indicating that the latter are reset or cooling ages. Potassic felsic intrusions are coeval with potassic mafic volcanic rocks (36.6 Ma to 33.4 Ma) in the same area, supporting a possible genetic link between the two end members. The dated intrusions occur over a 200 km wide zone across the Ailao Shan-Red River shear zone; therefore they are unlikely genetically related to shearing. Rather, potassic mafic magmatism in western Yunnan may be related to delamination and melting of previously subduction-modified mantle lithosphere along the Mesozoic Jinsha suture reactivated in the Eocene–Early Oligocene, following the India-Asia continental collision; potassic felsic magmas were crustal melts hybridized with mafic liquids. Delamination in turn facilitated and localized initiation of the Ailao Shan-Red River shear zone at ca. 32 Ma during continental extrusion.